Una manifestazione della chiesa sinodale: L'assemblea - Tangorra, Giovanni (Lateranum, 2022)
Starting from semantic affinities, the article develops a reflection on the theme of the assembly gathered in the context of synodality. The assembly is seen in itself, before being seen as an object, bringing out the self-awareness of a "baptismal we". The subject is addressed within an ecclesiological framework, raising questions about the relational principle, the concept of the Church as assembly, and the pneumatological dimension. Some peculiar traits are also noted, such as the relationship with mission. The aim is to validate the potential of the assembly in order to build a synodal Church, accrediting its epiphanic and actuative role. The question arises as to how to get out of its predominantly liturgical praxis.